A Scoping Review of Telehealth - Abbott, P. A.; Liu, Y. (Yearbook of Medical Informatics, 2013)
Objectives: This scoping review of the telehealth literature over the past year was conducted to provide a snapshot of some of the current developments in the field. As with any scoping review, only a subset of papers was examined, and the rigorous methods of a systematic review are not applied.Methods: We surveyed selected dimensions of the current literature, specifically targeting telehealth or eHealth interventions at the patient (or micro) level in this scoping review. Considering the lack of clarity around the terms like mHealth, eHealth, telehealth, and telemedicine, efforts were made understand and harmonize the terminology as part of the review process.Results: A total of 171 papers that matched the search criteria were culled from the literature. After discussion and debate, a total of 26 papers were retained and classified into at least one of 5 conceptual categories that were derived form a concept analysis. The five categories are Preventive and Therapeutic Effects; Health Service Utilization; Challenges & Opportunities for Enhanced User Centered Design; Low-powered studies/inconclusive evidence; and Future trends in telehealth. Each of these 5 concept categories are discussed to provide a better understanding of present opportunities, challenges, and the overall prospects for telehealth advancement.Conclusions: The field is expanding and maturing rapidly. There is a need for larger scale studies that balance rigor while reducing translational latency. Additional attention to implementation science methods is recommended as global telehealth projects accelerate.
Keywords: Telehealth; eHealth; implementation science; mHealth; global health